Peran Panel dan Appellate Body dalam Penyelesaian Sengketa di WTO - Methania, Terisa; Putri, Ratna Gayatri; Nurjanah, Rina; Syauqi, Rafi Dhias (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of the research is to determine the role of panels and the Appellate Body in resolving disputes at the WTO. The research method used in this paper is a research method with a normative juridical approach with descriptive-analytical research specifications. The dispute resolution mechanism in the WTO involves five main stages. The first stage is consultation, where the disputing countries try to resolve the problem directly. The second stage includes settlement efforts through good services, conciliation and mediation. The third stage is the establishment of a panel, where independent experts examine the dispute and prepare a report. The fourth stage is the appeals process, where the appeals body reviews the panel's decision if there is an appeal. The final stage is the implementation of the decisions and recommendations issued. The panel is formed within approximately 90 days of the application, consisting of independent experts selected by the DSB. The panel works based on the Terms of Reference (ToR) which regulate the procedures for resolving disputes and is tasked with carrying out an objective assessment of the problems faced, assisting the DSB in making recommendations. If consultations fail, the aggrieved country can request the formation of a panel from the Dispute Settlement Body (DSB). If the panel fails to reach a solution, they must submit a written report to the DSB. This process ensures dispute resolution within a certain time period to ensure legal certainty. In addition, there is an appeal mechanism through the Appellate Body which consists of seven international trade law experts. The appeal process must be completed within 90 days, and the Appellate Body report is final and must be adopted by the DSB.